Reproductive Tract infections and Premalignant Lesions of Cervix: Evidence from Women Presenting at the Cancer Detection Centre of the Indian Cancer Society, Delhi, 2000–2012 - Dey, Subhojit (J Obstet Gynaecol India, 2016)
OBJECTIVES: Burden of cervical cancer (CC) is highest for women in low- and middle-income countries (LMICs). Human papillomavirus (HPV) is implicated as the necessary cause of CC although a number of other factors aid the long process of CC development. One among them is the presence of reproductive tract infections (RTIs). This study investigated the associations between RTIs and CC from India. METHODS: This study utilized secondary data from the Cancer Detection Centre of the ICS, Delhi. Data were accessed from MS access database and were analyzed using MS Excel and SPSS 16.0. Multivariate analysis using unconditional logistic regression produced odds ratios (ORs) and 95 % confidence intervals (CIs). RESULTS: This study used data from 11,427 women over a period of 2000–2012. Women with RTIs had Candida, Trichomonas vaginalis (TV) or coccoid infections with all having similar prevalence (~4–5 %). 9.4 % of women had premalignant lesions of cervix; ASCUS was most common (7.9 %) followed by LSIL (1.3 %). TV was significantly associated with ASCUS, LSIL and all premalignant lesions of cervix (P < 0.001). Regression discovered an important association of TV with premalignant lesions of cervix (OR 2.79; 95 % CI 2.14, 3.64). CONCLUSIONS: Earlier studies have depicted associations between TV and HPV with possible enhancement of HPV virulence due to TV. Lack of awareness and hygiene, and limited access to gynecologists in LMICs lead to frequent and persistent RTIs which aid and abet HPV infection and CC occurrence. These also need to be addressed to reduce CC and RTIs among women in LMICs.